(untitled) (Research, Society and Development, 2025)
Studies indicate that tooth loss is still one of the main oral health problems faced by the Brazilian population, especially among the elderly. Therefore, the objective of this study was to carry out a data collection through the analysis of medical records and x-rays of the amount of tooth loss in patients over 50 years of age treated at a teaching clinic in Vale do Paraíba. In this way, a quantitative analysis was carried out among patients at the school clinic between 2020 and 2024, examining periapical and panoramic radiographs to record missing teeth and identify patterns of loss according to the position in the hidden arch, in addition to demographic and health data of the patients. The study analyzed 76 x-rays, finding that 100% of patients had tooth loss. The sample included 35 men (46.1%) and 41 women (53.9%), with a higher prevalence in the age group of 50 to 55 years. In men, 58.1% of losses were in the maxilla and 52.7% in the mandible, while in women, 41.9% were in the maxilla and 47.3% in the mandible. Patients using medications to treat cholesterol, depression, diabetes, thrombosis, anxiety, hypertension and cardiac arrhythmia were also identified. Therefore, despite advances in public health, tooth loss among the elderly is still high, the majority of which is caused by cavities, periodontal diseases and systemic conditions. Therefore, requiring preventive strategies and greater access to rehabilitative treatments to improve oral health and quality of life.